Fourth Five Year Plan Draft Outline Part-II Programme of Development - Planning Commission (Planning Commission, 1966)
Agricultural development programmes introduced in the first decade of-planning made a significant impact on the size and character of Indian agriculture. The growth rate in this sector represents a marked improvement over the performance in the preceding decades when the agricultural output grew by less than one per cent per annum. By contrast in the First Plan the annual rate of growth rose to 2.8 per cent. It increased further to 3,9 per cent in the Second Plan period. The index of agricultural production moved up from 96 in 1950-51 (bass: 1949-50) to 142 by the end of the Second Plan.
Planning Commission Government of India